Development Of Social Activity In Students Of Higher Educational Institutions - Kurbonova, Guzal; Ruzmetova, Xilola; Jumaev, Axmamat; Yarashev, Soli (The journal of contemporary issues in business and government, 2021)
In the world of higher education, it is important to improve the technology of development of social activity in the professional activity of students on the basis of cultural values, to create tools to support social activity and initiative of students, to improve the system of development of student social activity, to improve effective pedagogical mechanisms based on professional, cultural and communicative is doing.